Обробка інформації за допомогою динамічного хаосу - Корнієнко, Б.Я.; Устьянцев, А.В. (Збірник наукових праць Інституту проблем моделювання в енергетиці ім.Г.Є.Пухова НАН України, 2009)
The article deals with compression and encryption of information using dynamic chaos, given the results of the research work of the generator of chaotic oscillations in various modes.